Design and synthesis of unsymmetric macrocyclic hexaoxazole compounds with an ability to induce distinct G-quadruplex topologies in telomeric DNA. Issue 22 (16th May 2016) - Sakuma, Mai; Ma, Yue; Tsushima, Yamato; Iida, Keisuke; Hirokawa, Takatsugu; Nagasawa, Kazuo
Abstract : New macrocyclic hexaoxazole compounds bearing two side chains on an unsymmetrical macrocyclic ring system, i.e., 4, 2-L2H2-6OTD (2 ) and 5, 1-L2H2-6OTD (3 ), were designed as candidate G-quadruplex (G4) ligands and synthesized. Abstract : New macrocyclic hexaoxazole compounds bearing two side chains on an unsymmetrical macrocyclic ring system, i.e., 4, 2-L2H2-6OTD (2 ) and 5, 1-L2H2-6OTD (3 ), were designed as candidate G-quadruplex (G4) ligands and synthesized. These G4 ligands2 and3 induced an anti-parallel topology and a hybrid-type topology of telomeric DNA, respectively, in contrast to the previously reported symmetrical macrocycle 3, 3-L2H2-6OTD (1 ), which induces a typical anti-parallel structure. Molecular mechanics calculations and docking studies indicate that these differences arise from the different directions of the side chains in these L2H2-6OTD derivatives, and provide an explanation for the weaker stabilization of telomeric DNA by2 and3, compared with1 .